Preparation method of scenedesmus liquid-mediated synthesized carbon quantum dot nanofluid and oil-displacing agent

The carbon quantum dot nanofluid mediated by cephaloss liquid is solved by the low recovery rate of medium and low permeability reservoirs and the damage to formations of traditional oil dispersion technology, achieving efficient and environmentally friendly crude oil recovery effects.

CN119570470APending Publication Date: 2025-03-07YANGTZE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411741222.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Due to the small reservoir pores and complex structures of China's offshore medium and low permeability reservoirs, traditional oil displacement technology causes harm to the formation and has low recovery rates, so it is necessary to seek efficient and environmentally friendly development methods.

Method used

The preparation method of synthesis of carbon quantum dot nanofluids mediated by cephalossium liquid is adopted to form nano C-DOTs by reacting glacial acetic acid with phosphorus pentoxide, and the cephalossium liquid and ammonia water are added under magnetic heating and stirring to form a stable carbon quantum dot nanofluid.

Benefits of technology

The carbon quantum dot nanofluid obtained by this method has environmentally friendly and efficient oil displacement potential, which can greatly improve crude oil recovery and not cause harm to the formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570470A_ABST
    Figure CN119570470A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of scenedesmus liquid mediated synthesized carbon quantum dot nanofluid and an oil displacement agent. The preparation method comprises the following steps: preparing scenedesmus liquid; the preparation method comprises the following steps: preparing carbon quantum dots, taking glacial acetic acid as a carbon source, and reacting phosphorus pentoxide with glacial acetic acid to release heat to form nano C-DOTs; the preparation method comprises the following steps: adding pure water into nano C-DOTs, magnetically heating and stirring at 70 DEG C, and then adding scenedesmus liquid and a proper amount of NH3.H2O to obtain the scenedesmus liquid-mediated synthesized carbon quantum dot nanofluid. According to the preparation method and the oil-displacing agent, the nanofluid is obtained by adopting green bio-based liquid, and small organic molecules generated by organisms have the effect of stably dispersing nano particles; the biological nanofluid has environmental friendliness and efficient oil displacement potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bionano oil displacement, and specifically relates to a preparation method of carbon quantum dot nanofluid synthesized by means of Scenedesmus fluid and an oil displacement agent. Background Art

[0002] Some of the medium- and low-permeability oil reservoirs in China's offshore areas have small pores and complex structures. When the fluid seeps through them, it is strongly affected by the phase interface, which brings great difficulties to crude oil production. The overall crude oil production presents the phenomenon of "high water injection pressure, low recovery rate, and poor development effect". In addition, the chemical surfactants and polymer flooding in traditional recovery enhancement technologies will cause damage to the formation. Oil fields urgently need to seek more efficient and environmentally friendly development methods to solve the shortcomings of traditional recovery enhancement technologies.

[0003] Bio-nanotechnology combines nanoparticles with biomass to form a new type of composite material, which has both biological environmental protection and the uniqueness of nanomaterials, and has broad development prospects and application potential. Nanoparticles are small in size and can easily enter the tiny pores of the reservoir, without blocking the formation and reducing the permeability. At the same time, their high surface energy and unique structure can be adsorbed on the rock wall, peeling off the attached oil droplets and water film, expanding the pore size, and changing the wettability of the rock surface, which is conducive to increasing the injection of water injection wells and increasing the production of oil production wells. Biomaterials, as modifiers and dispersants on the surface of nanoparticles, can also solve environmental pollution problems and are conducive to sustainable development.

[0004] Traditional methods for synthesizing nanomaterials mainly include physical and chemical methods. Among them, physical methods such as sputtering, arc discharge and ball milling have high requirements on the instruments and equipment required for the reaction and consume a lot of energy; chemical methods such as microemulsion method, co-precipitation method and sol-gel method use reagents that are toxic, have poor degradability and are easy to cause environmental pollution.

[0005] Based on the above technical problems existing in the prior art, the present invention proposes a preparation method of carbon quantum dot nanofluid synthesized by Scenedesmus liquid and an oil displacement agent. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis and an oil-displacing agent in view of the deficiencies of the prior art.

[0007] The present invention adopts the following technical solution:

[0008] In a first aspect, a method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid is provided, comprising:

[0009] Step 1, preparing Scenedesmus solution;

[0010] Step 2, preparing carbon quantum dots, using glacial acetic acid as a carbon source, phosphorus pentoxide and glacial acetic acid react to release heat to form nano C-DOTs, wherein by weight: phosphorus pentoxide 7-10g, glacial acetic acid 4-5ml;

[0011] Step 3, add 185-190 ml of pure water to the nano-C-DOTs, stir under magnetic heating at 70°C, and then add 2-5 ml of the Scenedesmus solution and 3-5 ml of NH3·H2O, respectively, to obtain carbon quantum dot nanofluid synthesized by the Scenedesmus solution.

[0012] Further, step 1 comprises:

[0013] Step 1.1, preparing a culture medium, wherein the culture medium comprises:

[0014] 1.5g / LNaNO3,

[0015] 0.04g / LK2HPO4,

[0016] 0.075g / LMgSO4·7H2O,

[0017] 0.036g / L CaCl2·2H2O,

[0018] 0.02g / LNa2CO3,

[0019] 6mg / L citric acid,

[0020] 6mg / L ammonium ferric citrate,

[0021] 1mg / LEDTANa2,

[0022] 1ml / L trace elements A5, including: 2.86g / LH3BO3, 1.86g / L MnCl2·4H2O, 0.22g / LZnSO4·7H2O, 0.39g / LNa2MoO4·2H2O, 0.08g / LCuSO4·5H2O, 0.05g / LCo(NO3)2·6H2O;

[0023] The pH of the culture medium was adjusted to 7.1 with 1 mol / L NaOH and HCl, and then sterilized in a high pressure steam cooker at 121°C for 20 min. After natural cooling, the culture medium was inoculated with Scenedesmus.

[0024] Step 1.2, take the activated Scenedesmus species and add them to the culture medium, and continuously aerate and culture them for 20 days at 25°C and 1000-2000Lux light time for 12 hours a night, let the Scenedesmus liquid stand and settle for 48 hours, siphon off the supernatant, put the lower layer of Scenedesmus liquid into a centrifuge tube, adjust the centrifuge parameters to 4°C and 8000rpm for centrifugation for 15 minutes, discard the supernatant to collect the Scenedesmus, wash it thoroughly with deionized water for 3 times, and place it in a freeze dryer for 36 hours to obtain the Scenedesmus block, grind it into fine algae powder with a grinder, and then dissolve it in pure water to prepare 1% (w / v) Scenedesmus liquid, stir it with a magnetic stirrer at 90°C and 1000rpm for 1 hour, cool it to room temperature, and filter the extract with a vacuum pump, filter paper and suction filtration device to obtain pure Scenedesmus liquid.

[0025] Further, step 2 includes:

[0026] Step 2 includes: putting 8g of P2O5 into a beaker, adding 4ml of glacial acetic acid and 1ml of water, stirring with a glass rod for 1min to make it evenly dispersed, and standing for 10min to continue the reaction; adding pure water, stirring evenly to form nano C-DOTs, cooling to room temperature, adding water to the reaction mixture, standing at room temperature for 24h to settle, pouring out the upper clear liquid containing soluble ions, and repeating the operation five times to clean the C-DOTs.

[0027] Further, step 1 includes detecting the pigment composition of the Scenedesmus solution:

[0028] Take 10 ml of Scenedesmus solution, vacuum filter through a 0.45 μm microporous filter membrane, put the filter membrane into a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, cover the centrifuge tube cap, and soak in a 4 ° C refrigerator for 24 hours. Centrifuge at 8000 rpm and 4 ° C for 5 minutes to obtain the supernatant. Measure the absorbance of the supernatant at wavelengths of 645 nm, 663 nm, and 470 nm, and record them as A respectively. 663 , A 645 , A 470 , calculate total chlorophyll C according to the following formulas (1)-(4) a+b , Chlorophyll aC a , Chlorophyll bC b and total carotenoid C x-c content:

[0029] C a+b =20.2×A 645 +8.02×A 663 ...(1),

[0030] C a =12.21×A 663 -2.81×A 645 ……(2),

[0031] C b =20.13×A 645 -5.03×A 470 ……(3),

[0032] C x-c =(1000×A 470 -3.27×C a -104×C b ) / 229……(4).

[0033] Furthermore, in the tested Scenedesmus solution, the contents of C, H and N were 48.455%, 9.435% and 7.163%, respectively.

[0034] Further, the lipid content of the Scenedesmus liquid was detected: 0.05 g of freeze-dried Scenedesmus powder was weighed, and the mass was recorded as M1. The algae powder was dissolved in 10 ml of a 2:1 chloroform-methanol mixture, and after ultrasonication for 5 min, the mixture was water bathed at 45°C for 30 min. The mixture was filtered and poured into a 50 ml centrifuge tube, and then 2 ml of 0.9% NaCl solution was added. The mixture was centrifuged at 4°C and 3000 rpm for 10 min. The volume of the lower layer of liquid was recorded and recorded as V. A 5 ml dry and clean test tube was weighed and recorded as M0. 3 ml of the lower layer of liquid was drawn into the test tube, and the organic solvent was blown dry with N2 until it was completely volatilized. The mixture was dried in a 60°C oven to constant weight, and weighed after cooling to room temperature and recorded as M2. The lipid content of the algae cells was calculated according to formula (5):

[0035] LW(g / g)=(M2-M0)×V / (3×M1)……(5).

[0036] Further, step 1 includes detecting the crude protein C of Scenedesmus powder p And amino acid content:

[0037] C p = algal N content × 6.25;

[0038] Weigh 0.05g of Scenedesmus powder, put it into a hydrolysis tube, and add 10ml 6mol / L HCl, blow N230s into the tube and seal it, place it in an oil bath at 110℃ for hydrolysis for 24h, cool to room temperature, filter it with a 0.45μm filter membrane into a 50ml volumetric flask and make up the volume, take 2ml of the sample, place it on a rotary evaporator for deacidification at 45℃, dry it for 5-10min, add 2ml of sample buffer to fully dissolve it, and analyze it on a fully automatic amino acid analyzer. The test conditions are: buffer flow rate 20ml / h, reaction flow rate 10ml / h, separation column Na type cationic resin chromatography column, length and diameter 200×4.6mm, ultraviolet detection wavelength 570nm, 440nm, column temperature 55-65-77℃ program temperature rise, reaction tank temperature 138℃, injection volume 50μl, amino acids react with ninhydrin after separation on the separation column, the product can be detected by a spectrophotometer to obtain the concentration of amino acids.

[0039] Furthermore, step 3 includes characterization tests on the bio-nanofluid:

[0040] TEM was used to characterize the morphology and size of nanoparticles. The sample was dispersed in aqueous solution and ultrasonicated for 10 minutes. The dispersed liquid was dripped onto a copper mesh drop by drop. After drying, the sample morphology was photographed using TEM. Electrons were emitted from a thermal emission electron gun to image the sample penetration. The acceleration voltage was 200 kV and the thermal emission electron gun was a W filament. AFM was used to obtain the sample morphology and surface roughness information. The scanning mode was ScanAsyst in air. The liquid sample was dripped onto a silicon wafer and photographed with an instrument after drying.

[0041] FTIR was used to characterize the functional groups on the surface of nanoparticles and analyze the structure of biological organic matter. 1-2 mg of powder sample was evenly ground with 200 mg of pure KBr, pressed into a transparent sheet on a hydraulic press mold, and then placed in the instrument for testing. The wave number scanning range was 4000-400 cm -1 , set to scan 32 times, resolution 4cm -1 ;

[0042] XRD was used to characterize the key features of the crystal structure, grain size and atomic spacing of the nanoparticles. The powder sample was placed on a glass slide and tested using XRD. The test range was 2θ=5-90°, the scanning speed was 2° / min, the light source was Cu-Kα rays, the tube voltage was 40kV, and the current was 40mA.

[0043] XPS is used to determine the precise element ratio, chemical state and precise bonding properties of nanoparticles, identify the elements and their chemical state in or covering the material, and the vacuum degree of the analysis chamber is 8×10 -10Pa, selected Al ka ray excitation source, where hv = 1486.6 eV, set the working voltage to 12.5 kV, the filament current to 16 mA, the full energy spectrum test to 100 eV, the narrow spectrum to 20 eV, the step size to 0.05 eV, the dwell time to 40-50 ms, the etching conditions, use an argon ion gun to etch and thin the sample, the etching spot size is 1.5 mm, and the etching voltage is 3000 eV.

[0044] In a second aspect, a method for applying a carbon quantum dot nanofluid to improve crude oil recovery is provided.

[0045] In a third aspect, an oil displacing agent is provided, the oil displacing agent comprising carbon quantum dot nanofluid.

[0046] The beneficial effects of the present invention are:

[0047] The preparation method of the carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis and the oil-displacing agent of the present invention adopt green biological base liquid to obtain the nanofluid. The organic small molecules produced by the organisms have the effect of stabilizing and dispersing the nanoparticles. The biological nanofluid is environmentally friendly and has high-efficiency oil-displacing potential, and can greatly improve the crude oil recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1a-1b The method for preparing carbon quantum dot nanofluid synthesized by mediated by Scenedesmus liquid of the present invention is a schematic diagram showing the Zeta potential detection result of the particle size of the biological nanofluid;

[0049] Figure 2 The method for preparing carbon quantum dot nanofluid synthesized by mediated by Scenedesmus liquid of the present invention shows a Fourier infrared schematic diagram of biological nanomaterials;

[0050] Figure 3 The present invention is a method for preparing carbon quantum dot nanofluids synthesized by mediated by Scenedesmus liquid, and shows a schematic diagram of the asphaltene inhibition phenomenon of biological nanofluids. DETAILED DESCRIPTION

[0051] In order to more clearly understand the above-mentioned purposes, features and advantages of the present invention, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0052] Example 1

[0053] Embodiment 1 of the present application provides a method for preparing a Scenedesmus solution, comprising:

[0054] Step 1.1, preparing a culture medium, wherein the culture medium comprises:

[0055] 1.5g / LNaNO3,

[0056] 0.04g / L K2HPO4,

[0057] 0.075g / L MgSO4·7H2O,

[0058] 0.036g / L CaCl2·2H2O,

[0059] 0.02g / LNa2CO3,

[0060] 6mg / L citric acid,

[0061] 6mg / L ammonium ferric citrate,

[0062] 1mg / L EDTANa2,

[0063] 1ml / L trace elements A5, including: 2.86g / LH3BO3, 1.86g / L MnCl2·4H2O, 0.22g / LZnSO4·7H2O, 0.39g / LNa2MoO4·2H2O, 0.08g / L CuSO4·5H2O, 0.05g / L Co(NO3)2·6H2O;

[0064] The pH of the culture medium was adjusted to 7.1 with 1 mol / L NaOH and HCl, and then sterilized in a high pressure steam cooker at 121°C for 20 min. After natural cooling, the culture medium was inoculated with Scenedesmus.

[0065] Step 1.2, take the activated Scenedesmus species and add them to the culture medium, and continuously aerate and culture them for 20 days at 25°C and 1000-2000Lux light time for 12 hours at night, let the Scenedesmus liquid stand for 48 hours, siphon off the supernatant, put the lower layer of Scenedesmus liquid into a centrifuge tube, adjust the centrifuge parameters to 4°C and 8000rpm for centrifugation for 15 minutes, discard the supernatant to collect the Scenedesmus, wash it with deionized water for 3 times, and dry it in a freeze dryer for 36 hours to obtain the Scenedesmus block, grind it into fine algae powder with a grinder, and then dissolve it in pure water to prepare 1% (w / v) Scenedesmus liquid, stir it with a magnetic stirrer at 90°C and 1000rpm for 1 hour, cool it to room temperature, and filter the extract with a vacuum pump, filter paper and suction filtration device to obtain pure Scenedesmus liquid.

[0066] In an embodiment of the method for preparing the carbon quantum dot nanofluid of the present invention, the method comprises detecting the pigment components of the Scenedesmus fluid:

[0067] a. Detect the pigment components of the Scenedesmus liquid. Take 10 ml of the algae liquid, vacuum filter it through a 0.45 μm microporous filter membrane, put the filter membrane into a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, cover the centrifuge tube cap, and soak it in a 4°C refrigerator overnight for 24 hours. Then centrifuge it at 8000 rpm and 4°C for 5 minutes to obtain the supernatant. Measure the absorbance of the supernatant at wavelengths of 645 nm, 663 nm, and 470 nm, and record them as A respectively. 663 , A 645 , A 470 Calculate the total chlorophyll (C) according to the following formulas (1)-(4) a+b ), chlorophyll a (C a ), chlorophyll b(C b ) and total carotenoids (C x-c )content:

[0068] C a+b =20.2×A 645 +8.02×A 663 ...(1),

[0069] C a =12.21×A 663 -2.81×A 645 ……(2),

[0070] C b =20.13×A 645 -5.03×A 470 ……(3),

[0071] C x-c =(1000×A 470 -3.27×C a -104×C b ) / 229……(4),

[0072] b. Determination of C, H and N contents in Scenedesmus liquid, EA was used to determine the element contents in algae powder, and the high temperature combustion method was used to analyze the conventional organic element contents in the sample. Under high temperature aerobic environment, the organic element contents can be converted by the stable forms of CO2, H2O and N2 generated by combustion reaction. Under the condition of given sample weight, the amount of gas products produced after complete combustion was used and then converted into the corresponding amount, so that the contents of various elements in the sample were 48.455%, 9.435% and 7.163% respectively;

[0073] c. Determination of lipid content of Scenedesmus liquid: weigh 0.05g freeze-dried algae powder, record the mass as M1, dissolve it in 10ml 2:1 chloroform-methanol mixture, ultrasonicate for 5min, and place in a water bath at 45℃ for 30min. Filter the mixture and pour it into a 50ml centrifuge tube. Then add 2ml 0.9% NaCl solution and centrifuge at 4℃, 3000rpm for 10min. Record the volume of the lower layer liquid, record it as V, weigh a 5ml dry and clean test tube, record it as M0, draw 3ml of the lower layer liquid into the test tube, blow dry the organic solvent with N2 until it is completely volatilized, put it in a 60℃ oven to dry to constant weight, cool to room temperature and weigh it, record it as M2, and calculate the total lipid content (LW) of algae cells according to formula (5):

[0074] LW(g / g)=(M2-M0)×V / (3×M1)……(5),

[0075] d. Crude protein (C p ) and amino acid content were tested;

[0076] C p = algal N content × 6.25;

[0077] Weigh 0.05g of algae powder, put it into a hydrolysis tube, and add 10ml 6mol / L HCl, blow N2 into the tube for 30s and seal it, place it in an oil bath at 110℃ for hydrolysis for 24h, cool it to room temperature, filter it into a 50ml volumetric flask with a 0.45μm filter membrane and make up the volume, take 2ml of the sample, place it on a rotary evaporator for deacidification at 45℃, dry it for 5-10min, add 2ml of sample buffer to fully dissolve it, and analyze it on a fully automatic amino acid analyzer. The test conditions are: buffer flow rate 20ml / h, reaction flow rate 10ml / h, separation column Na type cationic resin chromatography column, length and diameter 200×4.6mm, ultraviolet detection wavelength 570nm, 440nm, column temperature 55-65-77℃ program temperature rise, reaction tank temperature 138℃, injection volume 50μl, detection method is that the amino acid reacts with ninhydrin after separation on the separation column, the product can be detected by a spectrophotometer to obtain the concentration of the amino acid;

[0078] e. TEM was used to characterize the morphology and size of nanoparticles. The sample was dispersed in aqueous solution and ultrasonicated for 10 minutes. The dispersed liquid was dripped onto the copper mesh drop by drop. After drying, the sample morphology was photographed using TEM. Electrons were emitted from a thermal emission electron gun to image the sample penetration. The acceleration voltage was 200 kV and the thermal emission electron gun was a W filament. AFM was used to obtain the sample morphology and surface roughness information. The scanning mode was ScanAsyst in air. The liquid sample was dripped onto a silicon wafer and photographed with the instrument after drying.

[0079] f. Use FTIR to identify the functional groups of Scenedesmus powder. Take 1-2 mg of powder sample and 200 mg of pure KBr and grind them evenly. Press them into transparent sheets on the mold of hydraulic press. Then put them into the instrument for testing. The wave number scanning range is 4000~400 cm -1 , set to scan 32 times, resolution 4cm -1 ;

[0080] XRD was used to characterize the key features of the crystal structure, grain size and atomic spacing of the nanoparticles. The powder sample was placed on a glass slide and tested using XRD. The test range was 2θ=5-90°, the scanning speed was 2° / min, the light source was Cu-Kα rays, the tube voltage was 40kV, and the current was 40mA.

[0081] XPS is used to determine the precise element ratio, chemical state and precise bonding properties of nanoparticles, identify the elements and their chemical state in or covering the material, and the vacuum degree of the analysis chamber is 8×10 -10 Pa, selected Al ka ray excitation source, where hv = 1486.6 eV, set the working voltage to 12.5 kV, the filament current to 16 mA, the full energy spectrum test to 100 eV, the narrow spectrum to 20 eV, the step size to 0.05 eV, the dwell time to 40-50 ms, and the etching conditions, using an argon ion gun to etch and thin the sample, the etching spot size to 1.5 mm, and the etching voltage to 3000 eV.

[0082] In an embodiment of the method for preparing the Scenedesmus liquid of the present invention, the Scenedesmus was purchased from the algae seed bank of the Institute of Hydrobiology, Chinese Academy of Sciences (Wuhan).

[0083] Example 2

[0084] Embodiment 2 of the present invention provides a method for synthesizing a bionanofluid, comprising:

[0085] S2.1, put 10g P2O5 into a 500ml beaker, add 5mL glacial acetic acid and 1ml water. A large amount of heat will be released in this process, and the temperature will rise rapidly. Stir slowly with a glass rod for 1min to make it evenly dispersed, let it stand for 10min to continue the reaction, then add 10ml pure water and stir evenly. The addition of water will cause P2O5 to continue to release heat, and the glacial acetic acid will be carbonized at high temperature to form nano C-DOTs. After cooling to room temperature, add 100mL water to the reaction mixture, let it stand for 24h at room temperature to settle, pour out the supernatant containing soluble ions, repeat the operation five times to clean the C-DOTs and obtain a black solid;

[0086] S2.2, add 180 ml of pure water to disperse the C-DOTs solid, stir under magnetic heating at 70°C for 30 min, add 20 ml of the obtained Scenedesmus solution and an appropriate amount of NH3·H2O, continue the reaction for 3 h, the organic small molecules and functional groups in the Scenedesmus solution are grafted and modified on the surface of C-DOTs, and the volume is fixed to 200 ml with pure water, and finally a stable carbon quantum dot nanofluid synthesized by Scenedesmus solution is obtained;

[0087] Characterization and testing of carbon quantum dot nanofluids synthesized by Scenedesmus fluid;

[0088] 1) TEM was used to characterize the morphology and size of the nanoparticles. The sample was dispersed in an aqueous solution and subjected to ultrasound for 10 min. The dispersed liquid was dripped onto a copper mesh drop by drop. After drying, the sample morphology was photographed using TEM. The accelerating voltage was 200 kV and the thermal emission electron gun was a W filament.

[0089] 2) AFM was used to obtain sample morphology and surface roughness information in the scanning mode ScanAsyst in air. The liquid sample was dropped on the silicon wafer and photographed after drying.

[0090] 3) FTIR was used to characterize the functional groups on the surface of nanoparticles and analyze the structure of biological organic matter. The test process was as follows: 1-2 mg of powder sample was evenly ground with 200 mg of pure KBr, pressed into a transparent sheet on a hydraulic press mold, and then placed in the instrument for testing. The wave number scanning range was 4000-400 cm -1 , set to scan 32 times, resolution 4cm -1 ;

[0091] 4) XRD was used to characterize the key features of the nanoparticles, such as crystal structure, grain size and interatomic distance. The test conditions were as follows: the powder sample was placed on a glass slide and tested using XRD. The test range was 2θ=5-90°, the scanning speed was 2° / min, the light source was Cu-Kα rays, the tube voltage was 40 kV, and the current was 40 mA.

[0092] 5) XPS is used to determine the precise element ratio, chemical state and precise bonding properties of nanoparticles, and to identify the elements and their chemical states within or covering the material. The test conditions are: the vacuum degree of the analysis chamber is 8×10 -10 Pa, selected Al ka ray excitation source (hv = 1486.6eV), set the working voltage to 12.5kV, the filament current to 16mA, the full spectrum test energy to 100ev, the narrow spectrum to 20eV, the step length to 0.05eV, the dwell time to 40-50ms, the etching conditions, the sample was etched and thinned using an argon ion gun, the etching spot size was 1.5mm, and the etching voltage was 3000eV;

[0093] Therefore, bionanofluids have Tyndall effect, viscosity <10cp, and good injectability, such as Figure 1a , Figure 1b As shown in the figure, the Zeta potential is -35.6mV. The Scenedesmus fluid contains a large amount of pigments, amino acids and lipid organic components, which improve the stability of the fluid. TEM shows that the nanoparticle size is less than 10nm, which is the size of quantum dots. AFM characterization shows that the height of carbon quantum dots is 2nm, with high roughness, showing a porous structure. Figure 2 As shown, FTIR shows that after modification, the carbon quantum dots form hydrogen bonds and have excellent water dispersion stability.

[0094] Example 3

[0095] Example 3 of the present application provides a wettability test method, comprising:

[0096] The quartz plate was rinsed and soaked in a mixture of ethanol and water for 24 hours, dried in a 60°C thermostat, immersed in crude oil for 7 days, taken out and dried in a fume hood, immersed in bio-nanofluids of different concentrations for 72 hours, immersed in water in the wettability measuring instrument, and crude oil was dripped on the lower surface of the quartz plate through a paper clip. The signal was amplified by a contact angle measuring instrument and the image was transmitted to a computer to observe the wetting angle;

[0097] Example 3 of the present application provides an experimental method for inhibiting asphalt deposition, comprising:

[0098] To obtain asphaltene, add 4g of heavy oil and 80g of n-heptane into a wide-mouth bottle, stir thoroughly with a glass rod for 15min and let stand for 24h. Theoretically, all components in crude oil except asphalt can be dissolved in n-heptane. Use a suction filtration device to filter the mixture of n-heptane and crude oil through ordinary filter paper to obtain a black asphaltene filter cake on the filter paper. Dry it in an oven for 24h and then extract it with toluene. Put the dried asphaltene filter paper into an extraction tube, introduce circulating water into the condenser, add the extractant toluene into the extraction bottle, and The temperature of the bottom heater is adjusted to 70℃, and the solvent vapor enters the extraction tube through the connecting tube and condenses into liquid under the action of the condenser. These liquids will dissolve asphaltene and return to the extraction bottle through the siphon tube at a certain interval. At this time, the extraction bottle is the toluene liquid that dissolves asphalt. The extraction process lasts for 5 hours until the liquid in the extraction tube becomes colorless and transparent. The mass m1 of the clean culture dish is weighed in advance, and the obtained asphalt-toluene liquid is poured into the culture dish and dried in an oven at 60℃ to obtain pure asphaltene. Weigh m2 again and calculate the mass of asphaltene.

[0099] Calibrate the asphaltene-toluene absorbance curve, dissolve asphalt with toluene solvent, prepare asphalt-toluene solutions with mass fractions of 0.01%, 0.05%, 0.1%, 0.25%, 0.5%, and 1.0%, respectively, measure the ultraviolet absorption spectra at different concentrations with UV-Vis, determine the appropriate wavelength to evaluate the absorbance, measure the absorbance of asphaltene at different concentrations at this wavelength, and draw the asphaltene-toluene absorbance curve;

[0100] To evaluate the inhibition of asphaltene precipitation, an appropriate concentration of asphalt-toluene solution was selected as the experimental reference, and 20%, 40%, 60%, 80% and 100% volume fractions of n-heptane were added respectively. The precipitation of asphaltene was analyzed by absorbance. On this basis, the synthetic bio-nanofluid was added to evaluate the inhibitory effect on asphaltene deposition.

[0101] Example 3 of the present application provides a macro oil washing experimental method, comprising:

[0102] Simulated formation water was prepared by dissolving 0.45g Na2SO4, 0.3g NaHCO3, 0.3g KCl, 0.75g MgCl2, 1.8g CaCl2, and 16.5g NaCl in 1L pure water, with a mineralization of about 21000mg / L. The mixture of oil and sand was placed in a beaker at a ratio of 1:10 (10g oil sand + 100g liquid), and aged in an oven at 60°C for 7 days, with occasional stirring to ensure that the mixture was fully mixed. The mixture of oil sand and oil displacement agent was placed in a wide-mouth bottle at a ratio of 1:10, and shaken on a shaker at 60°C and 300rpm for 48h. The oil sand and eluent were poured out, and the mass of the wide-mouth bottle and the remaining oil sand was weighed. The simulated formation water was used as a control experiment to analyze the difference in the oil washing results.

[0103] Embodiment 3 of the present application provides a microscopic oil stripping experimental method, comprising:

[0104] The quartz plate was pretreated at 90℃ for 1h, immersed in a mixed solution (concentrated H2SO4:H2O2=1:4) to remove residual organic impurities on the surface, washed with pure water for many times, dried for standby use, crude oil was dropped on the surface of the quartz plate, and it was quickly turned upside down in a square container filled with oil displacement agent to observe the changes of oil droplets;

[0105] After the above experiments, the surface of the quartz sheet treated with bio-nanofluid is hydrophobic and oleophobic, similar to the micro-nanopapillary structure on the surface of lotus leaves, which can provide water flow sliding effect and reduce the retention and adsorption of oil and water. Figure 3As shown, in the experiment of inhibiting asphaltene precipitation, it was found that nanofluids can improve the dispersion stability of asphaltene. When the added concentration reached 500 mg / L, the absorbance almost reached the maximum value. The bio-nanofluid showed extremely strong oil washing ability, which was 36.09 times higher than that of formation water, and had a self-cleaning effect of preventing crude oil from adhering to the glass wall. The bio-nanofluid had a very obvious stripping effect on oil droplets. The process can be described as the oil droplets being penetrated by nanoparticles and gradually "disintegrated", and the oil droplets attached to the surface of the quartz sheet were split into countless fine oil particles floating upward to form "oil filaments", and then gathered into a sheet-like oil film floating on the upper liquid surface. The oil displacement experiment simulation was carried out in a low-permeability core of 8 mD, and the recovery rate could be improved by 19.7%, and the oil displacement effect was significant. The carbon quantum dot nanofluid synthesized by the mediated synthesis of the Scenedesmus liquid provided by the present invention has obvious effect in the application of improving crude oil recovery rate and is environmentally friendly.

[0106] The present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principle of the present invention. Without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements, which are within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid, characterized in that: include: Step 1, preparing Scenedesmus solution; Step 2, preparing carbon quantum dots, using glacial acetic acid as a carbon source, phosphorus pentoxide and glacial acetic acid react to release heat to form nano C-DOTs, wherein by weight: phosphorus pentoxide 7-10g, glacial acetic acid 4-5ml; Step 3, add 185-190 ml of pure water to the nano-C-DOTs, stir under magnetic heating at 70°C, and then add 2-5 ml of the Scenedesmus solution and 3-5 ml of NH3·H2O, respectively, to obtain carbon quantum dot nanofluid synthesized by the Scenedesmus solution.

2. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid according to claim 1, characterized in that: Step 1 includes: Step 1.1, preparing a culture medium, wherein the culture medium comprises: 1.5g / LNaNO3, 0.04g / L K2HPO4, 0.075g / L MgSO4·7H2O, 0.036g / L CaCl2·2H2O, 0.02g / LNa2CO3, 6mg / L citric acid, 6mg / L ammonium ferric citrate, 1mg / L EDTANa2, 1ml / L trace elements A5, including: 2.86g / LH3BO3, 1.86g / L MnCl2·4H2O, 0.22g / LZnSO4·7H2O, 0.39g / LNa2MoO4·2H2O, 0.08g / L CuSO4·5H2O, 0.05g / L Co(NO3)2·6H2O; The pH of the culture medium was adjusted to 7.1 with 1 mol / L NaOH and HCl, and then sterilized in a high pressure steam cooker at 121°C for 20 min. After natural cooling, the culture medium was inoculated with Scenedesmus. Step 1.2, take the activated Scenedesmus species and add them to the culture medium, and continuously aerate and culture them for 20 days at 25°C and 1000-2000Lux light time for 12 hours at night, let the Scenedesmus liquid stand for 48 hours, siphon off the supernatant, put the lower layer of Scenedesmus liquid into a centrifuge tube, adjust the centrifuge parameters to 4°C and 8000rpm for centrifugation for 15 minutes, discard the supernatant to collect the Scenedesmus, wash it with deionized water for 3 times, and dry it in a freeze dryer for 36 hours to obtain the Scenedesmus block, grind it into fine algae powder with a grinder, and then dissolve it in pure water to prepare 1% (w / v) Scenedesmus liquid, stir it with a magnetic stirrer at 90°C and 1000rpm for 1 hour, cool it to room temperature, and filter the extract with a vacuum pump, filter paper and suction filtration device to obtain pure Scenedesmus liquid.

3. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 2, characterized in that: Step 2 includes: putting 8g of P2O5 into a beaker, adding 4ml of glacial acetic acid and 1ml of water, stirring with a glass rod for 1min to make it evenly dispersed, and standing for 10min to continue the reaction; adding pure water, stirring evenly to form nano C-DOTs, cooling to room temperature, adding water to the reaction mixture, standing at room temperature for 24h to settle, pouring out the upper clear liquid containing soluble ions, and repeating the operation five times to clean the C-DOTs.

4. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 1, characterized in that: Step 1 involves testing the pigment composition of the Scenedesmus solution: Take 10 ml of Scenedesmus solution, vacuum filter through a 0.45 μm microporous filter membrane, put the filter membrane into a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, cover the centrifuge tube cap, and soak in a 4 ° C refrigerator for 24 hours. Centrifuge at 8000 rpm and 4 ° C for 5 minutes to obtain the supernatant. Measure the absorbance of the supernatant at wavelengths of 645 nm, 663 nm, and 470 nm, and record them as A respectively. 663 , A 645 , A 470 , calculate total chlorophyll C according to the following formulas (1)-(4) a+b , Chlorophyll aC a , Chlorophyll bC b and total carotenoid C x-c content: C a+b =20.2×A 645 +8.02×A 663 ……(1), C a =12.21×A 663 -2.81×A 645 ……(2), C b =20.13×A 645 -5.03×A 470 ……(3), C x-c =(1000×A 470 -3.27×C a -104×C b ) / 229……(4)。 5. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 4, characterized in that: The contents of C, H, N in the tested Scenedesmus liquid were 48.455%, 9.435%, and 7.163%, respectively.

6. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 4, characterized in that: Detection of lipid content of Scenedesmus liquid: weigh 0.05g of freeze-dried Scenedesmus powder, record the mass as M1, dissolve the algae powder in 10ml of 2:1 chloroform-methanol mixture, ultrasonicate for 5min, and place in a 45℃ water bath for 30min. Filter the mixture and pour it into a 50ml centrifuge tube, then add 2ml of 0.9% NaCl solution, centrifuge at 4℃, 3000rpm for 10min, record the volume of the lower layer liquid, record it as V, weigh a 5ml dry and clean test tube, record it as M0, draw 3ml of the lower layer liquid into the test tube, blow dry the organic solvent with N2 until it is completely volatilized, put it in a 60℃ oven to dry to constant weight, cool to room temperature and weigh it, record it as M2, calculate the lipid content of algae cells according to formula (5): LW(g / g)=(M2-M0)×V / (3×M1)……(5).

7. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 2, characterized in that: Step 1 includes the detection of crude protein C in Scenedesmus powder p And amino acid content: C p = algal N content × 6.25; Weigh 0.05g of Scenedesmus powder, put it into a hydrolysis tube, and add 10ml 6mol / L HCl, blow N230s into the tube and seal it, place it in an oil bath at 110℃ for hydrolysis for 24h, cool to room temperature, filter it with a 0.45μm filter membrane into a 50ml volumetric flask and make up the volume, take 2ml of the sample, place it on a rotary evaporator for deacidification at 45℃, dry it for 5-10min, add 2ml of sample buffer to fully dissolve it, and analyze it on a fully automatic amino acid analyzer. The test conditions are: buffer flow rate 20ml / h, reaction flow rate 10ml / h, separation column Na type cationic resin chromatography column, length and diameter 200×4.6mm, ultraviolet detection wavelength 570nm, 440nm, column temperature 55-65-77℃ program temperature rise, reaction tank temperature 138℃, injection volume 50μl, amino acids react with ninhydrin after separation on the separation column, the product can be detected by a spectrophotometer to obtain the concentration of amino acids.

8. The method for preparing carbon quantum dot nanofluid synthesized by Scenedesmus liquid-mediated synthesis according to claim 1, characterized in that: Step 3 includes characterization tests of the bio-nanofluids: TEM was used to characterize the morphology and size of nanoparticles. The sample was dispersed in aqueous solution and subjected to ultrasound for 10 minutes. The dispersed liquid was dripped onto a copper mesh drop by drop. After drying, the sample morphology was photographed using TEM. Electrons were emitted from a thermal emission electron gun to penetrate the sample and form an image. The accelerating voltage was 200 kV and the thermal emission electron gun was a W filament. AFM was used to obtain the sample morphology and surface roughness information. The scanning mode was ScanAsyst in air. The liquid sample was dripped onto a silicon wafer and photographed with an instrument after drying. FTIR was used to characterize the functional groups on the surface of nanoparticles and analyze the structure of biological organic matter. 1-2 mg of powder sample was evenly ground with 200 mg of pure KBr, pressed into a transparent sheet on a hydraulic press mold, and then placed in the instrument for testing. The wave number scanning range was 4000-400 cm -1 , set to scan 32 times, resolution 4cm -1 ; XRD was used to characterize the key features of the crystal structure, grain size and atomic spacing of the nanoparticles. The powder sample was placed on a glass slide and tested using XRD. The test range was 2θ=5-90°, the scanning speed was 2° / min, the light source was Cu-Kα rays, the tube voltage was 40kV, and the current was 40mA. XPS is used to determine the precise element ratio, chemical state and precise bonding properties of nanoparticles, identify the elements and their chemical state in or covering the material, and the vacuum degree of the analysis chamber is 8×10 -10 Pa, selected Al ka ray excitation source, where hv = 1486.6 eV, set the working voltage to 12.5 kV, the filament current to 16 mA, the full energy spectrum test to 100 eV, the narrow spectrum to 20 eV, the step size to 0.05 eV, the dwell time to 40-50 ms, and the etching conditions, using an argon ion gun to etch and thin the sample, the etching spot size to 1.5 mm, and the etching voltage to 3000 eV.

9. Use of a carbon quantum dot nanofluid prepared by the method for preparing a carbon quantum dot nanofluid synthesized mediated by a Scenedesmus fluid according to any one of claims 2 to 8 in improving crude oil recovery.

10. An oil-displacing agent, comprising the carbon quantum dot nanofluid prepared according to the method for preparing the carbon quantum dot nanofluid synthesized through the mediating method of Scenedesmus fluid according to any one of claims 2 to 8.